In Vitro Study of Fermented Complete Feed by Using Sago Residues as Main Source Diet - Samadi, Samadi; Wajizah, Sitti; Usman, Yunasri (ANIMAL PRODUCTION, 2015)
Recently, fermentation of low quality feed such as agro industry by products has been widely applied to produce enriched animal feed and improve animal productivity. The purpose of this study was to evaluate in vitro digestibility of fermented complete feed by using agro-residues from sago starch processing industries as main source diet.  Feed was formulated on the basis of 40% sago residue and mixed with other ingredients (rice brand, coconut meal, bread by product, soybean meal and soybean hulls) to fulfill the requirement of sheep with 16,10% of CP, 2,80 Mkal ME/kg and TDN 60,88% based on calculation. Mineral and Urea were added in the complete feed to reach mineral and CP requirements of sheep.  Complete feed formulation was fermented by using 3 commercial fermentation products (Saus Burger Pakan® (SBP), Probion® and EM4®) for 21 days. Total and types of microbes from commercial fermentation products which were utilized in this study were not determined. Parameters measured in this study were pH, NH3, IVDMD (in vitro dry matter digestibility), IVOMD (in vitro organic matter digestibility) and VFA total. The model used for the statistical analysis was completely randomized design (CRD) with 4 treatments (control and 3 different commercial fermentation products) and 4 replications.  The results of this study indicated that administration of different commercial fermentation products into fermented complete feed based on sago residues significantly influenced (P<0.05) on pH, NH3, VFA total, IVDMD and IVOMD. Generally, commercial fermentation products mainly SBP produced better feed quality by improving the values of pH, NH3, VFA total, IVDMD and IVOMD. However, types and total microorganisms were needed to be determined before experiment.